1999
DOI: 10.1161/01.cir.100.suppl_2.ii-316
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Arch Reconstruction by Transluminally Placed Endovascular Branched Stent Graft

Abstract: Background-Recently, thoracic aortic stent grafting has emerged as an alternative therapeutic modality for patients with thoracic aortic aneurysms and aortic dissections. However, its application has been limited to descending thoracic aortic aneurysms distal to the aortic arch. We report our initial clinical experience of endovascular branched stent graft repair for aortic arch aneurysms. Methods and Results-Endovascular grafting with Inoue branched stent grafts was attempted for 15 patients with thoracic aor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
148
0
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(154 citation statements)
references
References 21 publications
1
148
0
5
Order By: Relevance
“…Renal SGs are yet not deployed and the most proximal aortic part not fully deployed. Branched SGs were also developed and many prototypes tested both experimentally and in clinical cases (Inoue et al 1999, Chuter et al 2005, Andersen et al 2005. The main advantage of branched SGs is that they can be used in aneurysmatic parts of the aorta where there is no apposition between the main SG and the native aortic wall.…”
Section: Figurementioning
confidence: 99%
“…Renal SGs are yet not deployed and the most proximal aortic part not fully deployed. Branched SGs were also developed and many prototypes tested both experimentally and in clinical cases (Inoue et al 1999, Chuter et al 2005, Andersen et al 2005. The main advantage of branched SGs is that they can be used in aneurysmatic parts of the aorta where there is no apposition between the main SG and the native aortic wall.…”
Section: Figurementioning
confidence: 99%
“…69 For even more proximal thoracic aneurysms involving the aortic arch, branched and fenestrated stent grafts are being developed to accommodate perfusion through the great vessels. 99,100 Although feasibility has been demonstrated, it is already apparent that the required implantation techniques would have to be highly complex and demand considerable technical expertise. Some centers have thus been investigating techniques to create fenestrations intraoperatively after device deployment and coverage of critical branches.…”
Section: Future Directionsmentioning
confidence: 99%
“…According to reports of stent-grafting concomitant with bypass-grafting to head vessels, the technical success rate and the mortality rate are 87% and 7-17%, respectively, 1,14 which means there is no advantage compared with our results obtained using fenestrated stent grafts without bypass-grafting. Branched stent graft for aortic arch aneurysm was reported several years ago 15 and although the concept is promising, it has not been widely accepted because of the high mortality rate and high incidence of postoperative cerebral infarction. Saito et al recently reported improved results without any stroke complication using a single-branched stent graft for distal aortic arch aneurysm.…”
Section: Discussionmentioning
confidence: 99%